MODELING AND THEORETICAL RESEARCH OF THERMOELECTRIC SYSTEM FOR INTRACOLAR HYPOTHERMIA - O. V. Evdulov; R. A. Magomadov; S. G. Magomedova; N. A. Nabiyev (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives The purpose of the article is to simulate and theoretical study of the thermoelectric system (TPP) for intracavitary hypothermia, the study of the processes occurring in it taking into account the influence of the parameters of the object of influence and characteristics of a thermoelectric battery (TEB). Method A physical model of thermal power plants for intracavitary hypothermia, consisting of two thermopiles, interconnected through an all-metal thermal bridge, equipped with an acting tip and a liquid heat exchanger is proposed. A quasi-stationary mathematical model of thermal power plants has been developed as a set of interconnected heat exchange systems, thermopile and heat conductor characterized by heat capacity, thermal conductivity and thermal resistance, which allows us to estimate the duration of the device output to the operating mode, taking into account the thermal properties of the biological object. Result The dependences of the temperature change of different parts of TPPs in time are obtained for the case of operation of the device in idling mode and in the presence of heat load. The temporal variation of the temperature of the object of influence, the conductor, the heat pipe and the heat exchanger at different currents of supply of thermopile and also for different values of the temperature of the liquid in the heat exchanger is considered. Conclusion It is established that without load, the temperature of the acting tip stabilizes in approximately 4–4.5 minutes. At the same time, an increase in the current strength of an additional thermopile from 5 to 15 A at the current supply of the main thermopile 50 A reduces the operating value of T from 235 K to 220 K. During the procedures, the required level of laryngeal tissue temperature decrease (273 K) can be achieved at the main power supply current and additional thermopile, respectively, equal to 25 and 10 A after 2 min. At a fixed temperature of the reference junctions of the main thermopile, the limiting decrease in the temperature of the acting tip is limited by the magnitude of the optimal thermopile current. It is possible to obtain deeper cooling at a given value of the supply current by reducing the temperature of the reference junctions of the main thermopile.